Current orthognathic surgery practices: a comprehensive survey from planning to discharge in oral and maxillofacial surgery - Bär, Anne-Kathrin; Pabst, Andreas; Bouffleur, Frederic; Thiem, Daniel G. E.; Werkmeister, Richard; Kesting, Marco R.; Heiland, Max; Al-Nawas, Bilal; Becker, Philipp (Journal of cranio-maxillofacial surgery, 2025)
Detailed information on orthognathic surgery (OGS) practices in Germany, including treatment modalities, surgical concepts, and perioperative care standards, is limited. This study analyzed current practices along the patient pathway, from preoperative planning to discharge, through a nationwide survey of the German Association of Oral and Maxillofacial Surgery using dynamic online questionnaires (up to 56 questions). Responses from 169 surgeons (response-rate 9.2%) revealed substantial variability in training, perioperative care, and digital workflow adoption. While 44.4% used a hybrid of digital and conventional planning methods, broader digital integration was limited by high costs and logistical challenges. Perioperative care varied, particularly in support concepts, blood management, and antibiotic prophylaxis duration, with shorter regimens (≤24h) more common at university-hospitals and private practices. However, 98% agreed on the use of prophylaxis. Surgical approaches were more standardized, with most respondents favoring pre-surgical orthodontics, third molar extraction before OGS, and the maxilla-first approach. Postoperatively, 76% transferred patients to standard care, with 3-5 days discharge times. Significant correlations were observed between surgeon experience, case volume, and improved outcomes, including reduced operative time and faster discharge. These findings underscore the need for standardized OGS protocols to enhance patient safety, optimize recovery, and ensure consistent practices across healthcare settings.